Resilience and coping-strategy in back chronic pain syndrome patients - Khodakivsky, Yu. S. (Journal of Education, Health and Sport, 2019)
In the article presented the results of the empirical study of resilience and coping strategies in chronic back pain syndrome (CBPS) patients are given. The problem was investigated depending on the variant of affective arrangement of psychopathological symptomatology: anxiously depressive and sensitively hostile. The analysis of the distribution of the examined by the integral indicator of personal resilience confirmed the established tendency concerning its deficit due to lack of all its components in the index group, compared with the comparison groups. A comparative analysis of the indicators of groups with anxiously depressive and sensitively hostile variant of the affective arrangement of psychopathological symptomatology showed a statistically significant difference with the prevalence of low levels in the anxiously depressive group and almost uniform distribution of the indicators of low and average levels with a prevalence of the average level with a tendency to low in the sensitively hostile examined. The negative relationship of resilience with depression, hostility, stress and unproductive coping strategies has shown that a low level of resilience is associated with a more frequent assessment of CBPS patients the situation as dangerous, as a life-threatening one, and oneself - unable to control it. That is what leads to a stressful situation, passivity and avoidance.